The impact on clinical outcomes of post-operative radiation therapy delay after neoadjuvant chemotherapy in patients with breast cancer: A multicentric international study. (December 2020) - Marta, Gustavo Nader; AlBeesh, Reem; Pereira, Allan A. Lima; Oliveira, Leandro Jonata; Mano, Max S.; Hijal, Tarek
Abstract: Introduction: Radiation therapy (RT) is frequently used for post-operative treatment in breast cancer (BC) patients who received preoperative systemic therapy (PST) and surgery. Nevertheless, the optimal timing to start RT is unclear. Material and methods: Data from BC patients who underwent chemotherapy as PST, breast surgery and RT at 3 Institutions in Brazil and Canada from 2008 to 2014 were evaluated. Patients were classified into three groups regarding to the time to initiation of RT after surgery: <8 weeks, 8–16 weeks and >16 weeks. Results: A total of 1029 women were included, most of them (59.1%; N = 608) had clinical stage III. One hundred and forty-one patients initiated RT within 8 weeks, 663 between 8 and 16 weeks and 225 beyond 16 weeks from surgery. With a median follow-up of 32 months, no differences in disease-free survival (DFS), overall survival and locoregional recurrence-free survival (LRRFS) were observed of time to indicated RT (<8 weeks versus 8–16 weeks versus >16 weeks). However, in luminal subtype patients (46.5%; N = 478), initiation of RT up to 8 weeks after surgery was associated with better LRRFS (<8 weeks versus >16 weeks: HR 0.22; 95%CI 0.05–0.86; p = 0.03), with a tendency to a better DFS (<8 weeks versus >16 weeks: HR 0.50; 95%CI 0.25–1.00). Conclusion: RT initiated up to 8 weeks after surgery was related to better LRRFS in luminal BC patients who underwent PST. Our results suggest that early start of RT is important for these patients. Highlights: RT is used for treatment in breast cancer patients who received chemotherapy as preoperative systemic therapy (PST). The optimal timing to start RT is unclear. RT initiated up to 8 weeks after surgery was related to better local control in luminal BC patients who underwent PST.